PEMANFAATAN ABU LIMBAH BONGGOL JAGUNG SEBAGAI BAHAN TAMBAH DENGAN VARIASI SUHU PEMBAKARAN TERHADAP KUAT TEKAN BETON - Achmad Rizco Hardiputranto; Kusno Adi Sambowo; Ririt Aprilin Soekarsono (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2021)
One way that can be done to reduce air pollution and production costs in concrete is by utilizing waste that is no longer used, one of which is by using corncob ash. The addition of corn cob ash is expected to make a positive contribution to the concrete, by providing adhesion to the concrete mixture so that it can increase the compressive strength. This study aims to determine the effect of adding corncob ash to the concrete mixture on temperature variations that will be used in burning corncobs. The compressive strength test was made using the standard method of SK SNI T-15-2000-03. All samples were made using a cube mold with dimensions of 15cm x 30cm. This test uses 36 samples consisting of normal concrete and 3 variations of corncob ash content ranging from 5%; 10%; 15%.. Based on the analysis of the compressive strength tester at the age of 28 days, the results were 19.67 MPa; 19.74 MPa; 21.81 MPa; 18.98 MPa. With an increase in the maximum compressive strength of 23.714 MPa at an optimum level of 10%. where the added material content of 10% has the highest compressive strength value compared to other corncob ash additions.